METODE PENGINJILAN TERHADAP ANAK PUNK DI KOMUNITAS CROSSLINE FAMILY - Stephen, Raymond; Handoko, Yusuf Slamet (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2022)
An evangelistic mission can be successful if it is carried out contextually. One of the mission agencies that has successfully carried out contextual evangelism is the Crossline Family, which carries out a mission to punk children. This study explores the evangelism method used by Crossline Family to punk children. The method used is descriptive qualitative. Informants are leaders and members of the Crossline Family. The writer collected data through interview techniques and analysis of the Crossline Family service journey history, which is documented via video. The study found that Crossline Family uses three methods in evangelizing punk children: 1) relate without judgment, 2) be proactive in being in the midst of their lives and be role models, and 3) convey God's Word through the genre of punk children's songs.